2023
DOI: 10.1111/iwj.14300
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of surgical wound infection and related factors in patients after long bone surgery: A systematic review and meta‐analysis

Abstract: The goal of this systematic review and meta‐analysis is to provide an overview of the prevalence of surgical wound infection and related factors in patients after long bone surgery. A comprehensive, systematic search was conducted in different international electronic databases, such as Scopus, PubMed, Web of Science and Persian electronic databases such as Iranmedex and Scientific Information Database using keywords extracted from Medical Subject Headings such as “Prevalence”, “Surgical wound infection”, “Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
2
1
Order By: Relevance
“… 3 The findings from another systematic review and meta‐analysis revealed that the occurrence of SSI among patients following long bone surgery is 3.3%. 11 The variance in the prevalence of orthopaedic SSI between our study and these previous investigations can be attributed to the differences in surgical site locations. In 2019, a systematic review and meta‐analysis were undertaken to examine the incidence of deep SSI following periarticular knee fracture repair.…”
Section: Discussioncontrasting
confidence: 38%
See 2 more Smart Citations
“… 3 The findings from another systematic review and meta‐analysis revealed that the occurrence of SSI among patients following long bone surgery is 3.3%. 11 The variance in the prevalence of orthopaedic SSI between our study and these previous investigations can be attributed to the differences in surgical site locations. In 2019, a systematic review and meta‐analysis were undertaken to examine the incidence of deep SSI following periarticular knee fracture repair.…”
Section: Discussioncontrasting
confidence: 38%
“…In orthopaedic surgery, a surgical site infection (SSI) is characterized as an infection that develops within 30 days following surgery when no fixation devices have been implanted, or within 1 year if a metallic device remains implanted. 1 , 2 , 3 , 4 SSI represents a prevalent complication in both orthopaedic and various other surgical procedures. The elevated incidence of SSI can be attributed to factors such as the expanding range of orthopaedic indications, the intricate nature of orthopaedic surgeries and the frequent use of implants in these procedures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation